Espaço geográfico e territórios de conflitos : demarcação e posse da Zona de Expansão Urbana de Aracaju/SE - Santos, Juliana Souto (2015)
This study aimed to analyze the characteristic spatial conflicts of territorial demarcation and ownership in Urban Expansion Area of Aracaju, considering the power relations and territoriality giving rise to legal proceedings between São Cristóvão and Aracaju. From this perspective, geopolitical categories were used, space, territory, multiterritoriality and spatial conflicts that underlie this doctoral thesis. The historical and analytical methods were applied to achieve the proposed subject matter. The main instruments of primary data collection were questionnaires with the population of the localities involved, as well as interviews with managers, politicians, historians both Aracaju as of São Cristóvão. In addition, historical documents in municipal and state archives were consulted. Secondary data were also raised about the two municipalities, as well as intense bibliographic review of the categories that support the study. Studying the spatial conflicts and the management of territories in Aracaju Expansion Zone shows the network of relations with historical and economic roots, political settings and symbolic identities that constitute a spatial mosaic, socially constructed. At present, the territory disputed by São Cristovão and Aracaju / SE, is still 'sub judice' and is one of the areas whose interests refer to both the public sphere and the private. The Aracaju municipal public sector has one of the options for widening its territory (physical basis) with the insertion of the Urban Expansion Area (created by Law 873/82), as well as tax revenue, in addition to receiving royaltes, being responsible for the provision of services and infrastructure endowment, which has made, albeit insufficient. The São Cristovão municipal power, which allowed the appropriation of the area by the current capital of Sergipe, is using the courts to resume possession of the territory and to thus be able to enjoy again the benefits of taxation and receive royaltes, a new possibility of income for the city But should take over the administration of the area, which certainly will constitute a difficulty, depending on the distance from headquarters. The private sector also benefits through the landowners and real estate market with the fragmentation of land subdivisions and construction of residential condominiums, plus the installation of commercial enterprises and services. The resident population has complained before of the difficulties, however, it is in favor of maintaining the territory with the municipality of Aracaju, considering the possibilities for improvement of infrastructure conditions of the area, in addition to membership issues, territoriality.